Posterior Capsule Opacification (PCO) - Nadia Aulia; Syarifah Rohaya (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Posterior Capsule Opacification (PCO), also known as secondary cataract, is the most common complication following cataract surgery, particularly extracapsular cataract extraction (ECCE). PCO results from the proliferation, migration, and differentiation of residual lens epithelial cells within the posterior capsule, leading to the formation of structures such as Elsching pearls and Soemmering rings. The incidence of PCO is notably high among pediatric patients due to the increased mitotic activity of lens epithelial cells. Major risk factors include younger age, certain ocular conditions such as glaucoma and age-related macular degeneration, as well as the design and material of the implanted intraocular lens (IOL). Diagnosis is established through slit-lamp and ophthalmoscopic examinations, with decreased visual acuity being the primary clinical symptom. The current mainstay of treatment is Nd:YAG laser capsulotomy, which is effective and minimally invasive but may be associated with complications such as cystoid macular edema and retinal detachment. Preventive strategies focus on improved surgical techniques and appropriate IOL selection. With proper intervention, the incidence of PCO can be reduced, thereby improving postoperative visual outcomes.